Pola Asuh Orang Tua dalam Menumbuhkan Akidah pada Anak Usia Dini - athfal stainu; Indah Puspa Haji (Al Athfal : Jurnal Kajian Perkembangan Anak dan Manajemen Pendidikan Usia Dini, 2018)
The more rapid development of the times and the increasingly sophisticated information media in this era of globalization, has become a challenge for parents in nurturing and educating their children, especially in providing religious education. Religious education is the basic education that must be taught to children from an early age, especially education about aqeedah as the foundation for the education of faith and Islamic teachings from an early age. If the faith has been good, then all the deeds will be good. Parenting in growing aqidah in early childhood is a process of interaction between parents and children, which includes activities such as maintaining, protecting, and directing children's behavior to grow faith in early childhood. The right parenting style for early childhood is authoritative parenting because in this parenting style parents value children personally by giving a sense of responsibility based on the rules. In this case parents can apply religious rules to children in order to grow their faith in children from an early age. In growing faith in early childhood there are various ways that are done by both parents, namely: educating through habituation, exemplary, advice and praise / rebuke. There are several factors that influence the process of growing faith in early childhood, namely: the media, peers and family.